POVERTY AS CHILD LABOR INTERNAL MIGRATIONâS DETERMINANT - Nurwita, Eva; Rinaldi, Rullan (Journal of Indonesian Economy and Business, 2009)
Migration is an unavoidable problem for economic development in third worldÂ countries. Indonesia is an archipelagic country with high viscosity population internalmigration. Over flooding wave of internal migration from periphery region to the core ofÂ growth poles increases the spatial disparities between regions. Not only for the labor forceÂ at their productive age, empirical evidences revealed the fact that the wave also involvedÂ children to work as child labor. This research tries to estimate how poverty in peripheryÂ determines the wave of migration toward urban agglomeration region at their core. UsingÂ data from the Indonesian Census 2000 for Java Island, global spatial effect and localÂ statistics was estimated by spatial econometrics method.Keywords: Child Labor, Internal Migration, Spatial Econometrics, urban agglomeration